Analysis of Factors Influencing QRIS Usage Decisions among Generation Z in Sekadau Regency - Riska Juliarsih (SEAN Institute, 2026)
Study This aim For analyze factors that influence decision QRIS usage among Generation Z in the Regency Sekadau . Research motivated by the increasing use digital payments in Indonesia, especially QRIS, but Still there is difference level use and acceptance technology in society area. Research This use approach quantitative with design study associative . Data collected through distribution questionnaire to 150 respondents Generation Z who ever using QRIS in the Regency Sekadau . Technique of taking sample use purposive sampling . Variables study covering perception benefits , perceptions convenience use , influence social and security transaction to decision QRIS usage . Data analysis was carried out use method Structural Equation Modeling – Partial Least Square (SEM-PLS) with SmartPLS 4 software assistance . Research results show that perception benefits , perceptions convenience use , influence social and security transaction influential positive and significant to decision QRIS usage in Generation Z. Perception benefit become the most dominant variable in influence decision QRIS usage . Findings This show that Generation Z tends to using QRIS because considered practical , efficient , easy used , as well as own system secure transactions . In addition , the influence environment social also participates push use of QRIS as part from style digital life of modern society . Research This give contribution theoretical in development of acceptance models technology based on TAM and UTAUT in context digital payments in the region developing . In practical , results study can become material consideration for government , banking , and providers service digital payments in increase literacy digital finance , quality services and security QRIS transactions in the community , especially Generation Z.